Digital integrated dramatherapy: A feasibility study in women undergoing assisted reproductive technology - Cercato, Maria Cecilia; Pierpaoli, Sandra; Pazienza, Rosa Maria; Terrenato, Irene; Guadagnuolo, Cinzia; Cenci, Cristina; Nappi, Rossella E. (Frontiers in Psychology, 2022)
Background: Dramatherapy is a practice of working and playing that uses action methods to facilitate creativity, imagination, learning, insight and growth. Methods: A pilot study of Digital Integrated Dramatherapy in arts, recruiting women from the digital community “Parole Fertili”, undergoing assisted reproductive technology. On the basis of a previous blended experience, a program based on remote sessions was conducted on a dedicated platform. Results: A total of 22 women participated in three groups. Participants assessed the feasibility and utility of the method, both in the synchronous and the asynchronous phases. The group has a fundamental role: the participants were supportive, and therapeutic benefits were due to strengthening and resiliency obtained through a dialogue with other women. Using metaphors, the participants could move from the narration of the ART pathway to creative and corporeal expression. Conclusions: The study showed that group based on Digital Arts Therapies might help women face very difficult emotions by promoting creativity and internal resources.